Physiological, perceptual and affective responses to high-intensity interval training using two work-matched programs with different bout duration in obese males - Spyridon Tsirigkakis; Yiannis Koutedakis; George Mastorakos; Pinelopi S. Stavrinou; Vassilis Mougios; Gregory C. Bogdanis (Elsevier, 2022)
Background/Objectives: This study compared physiological, perceptual, and affective responses to high-intensity interval training (HIIT) between two work-matched programs with different bout durations in obese males. Methods: Sixteen low-to-moderately active obese men completed an eight-week cycling program of supervised HIIT (3 days/week) using either short bouts [48 × 10 s at 100% of peak power output (PPO) with 15 s of recovery (HIIT10)] or long bouts [8 × 60 s at 100% PPO with 90 s of recovery (HIIT60)]. Workload was progressively adjusted, to maintain high intensity (100% PPO), throughout training. Blood lactate (BLa), heart rate (HR), ratings of perceived exertion (RPE), and feeling scale ratings (pleasure/displeasure) were measured in each HIIT session. Results: Average HR decreased in the last 2 weeks of training in both groups by 2.2 ± 1.8% of peak HR (p < 0.001). Training resulted in a reduction in BLa during exercise by 28 ± 19% (p < 0.001) from the 10th min onward only in HIIT10. Similarly, during the last weeks of training, RPE decreased (by 1.0 ± 1.1 units, p < 0.05) and feeling scale ratings were improved only in HIIT10, while RPE remained unchanged and feeling scale ratings deteriorated in HIIT60 (from 3.0 ± 1.1 to 2.1 ± 0.9 units, p < 0.001). No differences in post-exercise enjoyment were found. Conclusion: Both HIIT formats induced similar HR adaptations, but improvement of BLa, perceptual and affective responses occurred only when bout duration was shorter. Our findings suggest that, in low-to-moderately active obese men, HIIT may be more effective in improving metabolic, perceptual, and affective responses when shorter, rather than longer, bouts of exercise are used.